Identification and analysis of the myosin superfamily in Drosophila: a database approach. - Yamashita, R.A.; Sellers, J.R.; Anderson, J.B. (Journal of Muscle Research and Cell Motility, 2000)
The recent sequencing of the genome of Drosophila melanogaster has provided a valuable resource for mining the database for genes of interest. We took advantage of this opportunity in an attempt to identify novel myosins in Drosophila and confirm the presence of the previously identified myosins from classes I, II, III, V, VI, and VII. The Drosophila database annotators predicted the structure of three additional proteins which we identified as novel unconventional myosins, two of which fell into classes XV and XVIII, respectively. Our own efforts predicted the presence of four additional partial sequences that appear to be myosin proteins which did not fall into any specific class. In the future comparative genomics will hopefully lead to the placement of these myosins into new classes.